2023
DOI: 10.1001/jamanetworkopen.2023.0589
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of COVID-19 in Nightlife, Household, and Health Care Settings in Tokyo, Japan, in 2020

Abstract: ImportanceThere have been few studies on the heterogeneous interconnection of COVID-19 outbreaks occurring in different social settings using robust, surveillance epidemiological data.ObjectivesTo describe the characteristics of COVID-19 transmission within different social settings and to evaluate settings associated with onward transmission to other settings.Design, Setting, and ParticipantsThis is a case series study of laboratory-confirmed COVID-19 cases in Tokyo between January 23 and December 5, 2020, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…No nosocomial infection among healthcare providers was observed at our institution. In contrast, nosocomial infections were frequently observed during the same period in Japan [ 29 ]. We used not only this scoring method but also other infection control measures, such as education for staff and self-quarantine.…”
Section: Discussionmentioning
confidence: 99%
“…No nosocomial infection among healthcare providers was observed at our institution. In contrast, nosocomial infections were frequently observed during the same period in Japan [ 29 ]. We used not only this scoring method but also other infection control measures, such as education for staff and self-quarantine.…”
Section: Discussionmentioning
confidence: 99%
“…With extensive facility closures at tier 1, the halting of community activities had likely further compelled SARS-CoV-2 transmissions within the residence [ 25 ]. Such an epidemiological transition was mirrored in the outbreak dynamics, in which the precipitous rise mimicked the multiple infections established in fully susceptible households, whereas the exponential decline resulted from the limited onward transmission preempted by isolation [ 10 ]. In hindsight, discouraging multihousehold gatherings could be an effective means to confine the epidemic spread when new infections surge in the community [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the nature of social contacts in different settings could also play an important role in affecting the level of virus exposure and infection risk. Based on contact-tracing data, the transmission dynamics of SARS-CoV-2 can also be observed to be largely variable among clusters of infection emerging from different environments [ 8 - 10 ]. Yet, evidence formally appraising the association between exposure and outbreaks in a broader community context remains scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in a study in which some of the authors were members of the Japanese government's Subcommittee on Novel Coronavirus Disease Control, Imamura et al have reported that prioritizing surveillance and intervention in nightlife settings was effective in preventing the spread of COVID‐19, particularly in the early stages of the outbreak. 2 This conclusion was based on the surveillance of infection rates in Tokyo from January 23 to December 5, 2020, when vaccinations had not yet been administered. 2 However, during this investigation period, PCR testing was limited to those with severe symptoms, inevitably overlooking asymptomatic individuals or those with mild symptoms.…”
mentioning
confidence: 99%
“… 2 This conclusion was based on the surveillance of infection rates in Tokyo from January 23 to December 5, 2020, when vaccinations had not yet been administered. 2 However, during this investigation period, PCR testing was limited to those with severe symptoms, inevitably overlooking asymptomatic individuals or those with mild symptoms. Consequently, relying on the reported data from Japan during this period may result in an underestimation of the number of infections.…”
mentioning
confidence: 99%